Analytical model of structures with frictional pendulum isolators. - Almazan, Jose L. (Earthquake engineering & structural dynamics.)
This investigation centres on the development of a mathematically formal description of the dynamic response of structures isolated with the frictional pendulum system (FPS). It is shown that a theoretically 'exact' model can be formulated to account for large deformation kinematics and the associated P-A effects in the isolators. The problem is of importance in light of the large deformations observed during impulsive ground motions like those that occured during the Northridge, Kobe, Turkey and Taiwan earthquakes. Besides, the model developed may be easily extended to other devices with kinematic constraints other than the spherical one corresponding to the FPS. Results of the model are presented for two building examples. The first one deals with the seismic response of a rigid superstructure supported on two FPS isolators and is intended to provide a numerical example of the equations developed in the text. The second example presents the three dimensional earthquake response of a nominally symmetric structure supported on four FPS isolators and subjected to different ground motions. Both examples point out that small deformation kinematics may lead, in the case of impulsive motions, to discrepancies in global response quantities, relative to the 'actual' response, as large as 30 percent. These discrepancies increase up to 50 percent for local response quantities such as normal isolator forces.